Lithuanian Election 2016:the Mainstream Left and Right Rejected by Voters Angry with the Establishment - Valentinavicius, Virgis (Political Preferences, 2017)
In the 2016 Lithuanian parliamentary election the established political parties suffered an unexpected andcrippling defeat at the hand of the Lithuanian Peasant and Green Union (Lietuvos valstiečių ir žaliųjų sąjunga, LVŽS), a populist one-size-fits-all formation. The traditionalmessage of the establishment parties to take care of the economy, to advance foreign investment and improve business climate did not appealto voters, while the LVŽS made a pointof talking about issues people wanted to hear: the need to tackle social exclusion and poverty; to addresstheprivileged position of big business; to fight endemic corruption; to deal with the underfunding of education and culture. The electoral message of the winner combines the hard left promise of radical change on socioeconomic issues and the far right conservative approachto identity politics, human rights, minority rights, gender equality, and refugees. The LVŽS did its best to look as an anti-establishment, anti-party politics force, a loose and wide amalgam of contrastingpersonalities and contradicting messages. At the same time, the major factor behind the ‘revolutionary’ victory for radical change seems to be the inability of the mainstream parties to sense the change of sentiment of the electorate and to addressthe growing grievances of the public. The Lithuanian anti-establishment revolt is being compared with Donald Trump’s victory in the US, Brexit in the UK, Poland after the last election in 2015, and Hungary under Victor Orban. Key words: Lithuanian politics, Lithuanian election, party politics, populism, establishment, radicalism